Bioscience and the Good Life - Brassington, Iain (Bloomsbury Academic, 2012)
The field of biotechnology has provided us with radical revisions and reappraisals of the nature and possibilities of our biological existence. Yet beyond its immediate utility, does a life healthier, longer, or freer from disease make us